PENGEMBANGAN MODEL PELATIHAN AKUNTANSI DALAM UPAYA MENINGKATKAN KOMPETENSI KEUANGAN PADA UMKM WIRAUSAHAWAN MUDA - rakhmawati, ita (BISNIS, 2018)
Small medium enterprises is one of the perpetrators of the economic potential in Indonesia, both in terms of number and its contribution to the national economy. This event will be based on research by the large number of potential young entrepreneurs for small medium enterprises that develop among the students of business management Course Shari'a. However, the potential of encountering problems one is difficult because of the limited structure and capability still managing their finances. The purpose of this research is to know the financial competency mapping and owned by small medium enterprises run by young entrepreneur. Further based on the database used to compile the proper accounting training design. Primary data obtained from in-depth interviews, questionnaires and observation directly. Financial competence that is owned by young entrepreneurs for small medium enterprises can be seen from the source variable capitalization, turnover, business profits and the ability of the application of accounting in the form of presentation of the financial statements. The results showed that most small medium enterprises have difficulty in the sector as well as a good amount of capitalization capital structure. small medium enterprises operational views of the turnover and operating income showed a fairly progressive conditions for businessmen beginners. While the ability of drawing up financial statements still minimal, more that just make a simple cash flow report